2023
DOI: 10.3390/cancers15061764
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Squamous Cell Carcinoma in Immunocompromised Patients—A Comparison between Different Immunomodulating Conditions

Abstract: Background: Immunosuppression is strongly associated with an increased risk of developing cutaneous squamous cell carcinoma (cSCC). Studies on solid organ transplant recipients (SOTR) and chronic lymphocytic leukemia (CLL) patients have already demonstrated higher rates of aggressive cSCC tumors in these populations compared to immunocompetent controls. Studies on other immunosuppressed patient groups are scarce. This study was aimed at assessing the effects of different immunomodulating conditions on patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…However, several studies have reported increased β-HPV replication in the skin and greater β-HPV seropositivity in cSCC patients, which suggest a potential role for viral oncogenesis [ 18 ]. More importantly, the increased incidence of cSCC with concomitantly higher rates of β-HPV amongst solid organ transplants suggests a role for anti-β-HPV immunity in carcinogenesis [ 10 , 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have reported increased β-HPV replication in the skin and greater β-HPV seropositivity in cSCC patients, which suggest a potential role for viral oncogenesis [ 18 ]. More importantly, the increased incidence of cSCC with concomitantly higher rates of β-HPV amongst solid organ transplants suggests a role for anti-β-HPV immunity in carcinogenesis [ 10 , 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Immunosuppression profoundly elevates the risk of cancers associated with viral infection, including cSCC. Immunosuppressed patients have up to 100-fold higher cSCC rates compared with the general population [ 10 , 11 , 12 , 13 ]. Antiviral immunity is chiefly regulated by the adaptive immune system, where T cells orchestrate effective long-lived responses.…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppression is a medical condition strongly linked to cSCC development. Immunocompromised patients are significantly younger at the time of cSCC diagnosis, compared with non-immunocompromised cSCC patients (68 vs. 78 years), display higher recurrence rates (24% vs. 15%) and have more often multiple cSCCs (28% vs. 10%) [ 117 ]. The association between immunosuppression and cSCC risk was reported for several underlying conditions like chronic lymphocytic leukemia (4.82 fold increased cSCC risk) or HIV (5.40 fold increased cSCC risk), but it is especially strong for solid organ transplant recipients (OTR) [ 67 , 118 ].…”
Section: Risk Factors For Cutaneous Squamous Cell Carcinomamentioning
confidence: 99%
“…Non-melanoma skin cancer (NMSC) stands as one of the most prevalent forms of cancer globally, with cutaneous squamous cell carcinoma (cSCC) accounting for approximately 20% of all NMSC cases, placing it as the second most common type of epithelial malignancy. The incidence of skin cancers continues to increase, and it is well-known that chronic exposure to UV radiation (UVR) from sunlight is the main risk factor [ 1 , 2 ]. cSCC arises from epidermal keratinocytes, and non-UVR risk factors such as older age, fair skin, immunosuppression, and exogenous chemical mutagens are relevant in its development [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%